A hybrid nanocomposite material Zn-BTEC@ZIF-8 and its preparation method and fluorescent probe and detection method

By developing Zn-BTEC@ZIF-8 nanocomposite and its built fluorescent probe Zn-BTEC@ZIF-8@Tet, the problem of complex and time-consuming detection of histamine levels in food in the prior art is solved, and the problem of realizing the Fast and low-cost histamine detection.

CN116445156BActive Publication Date: 2025-02-14INST OF ENVIRONMENTAL MEDICINE & OCCUPATIONAL MEDICINE ACAD OF MILITARY MEDICINE ACAD OF MILITARY SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310229822.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2025-02-14
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

The prior art has problems such as complex sample preparation, expensive instruments, and long detection time when detecting histamine levels in food, making it difficult to achieve fast and low-cost detection.

Method used

A hybrid nanocomposite Zn-BTEC@ZIF-8 was developed and a fluorescent probe Zn-BTEC@ZIF-8@Tet was constructed based on its aggregation-induced luminescence effect with tetracycline, which was used to detect the histamine content in fish.

Benefits of technology

A rapid quantitative detection of histamine levels was achieved, the fluorescence intensity was stable within 20 minutes, and the stable storage time was more than 20 days, with a larger detection range and lower detection limit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116445156B_ABST
    Figure CN116445156B_ABST
Patent Text Reader

Abstract

The invention discloses a hybrid nanocomposite material Zn-BTEC@ZIF-8 and a preparation method thereof, a fluorescent probe and a detection method thereof. The Zn-BTEC@ZIF-8 is formed by coupling ZIF-8 on the surface of Zn-BTEC; the particles of Zn-BTEC are in irregular blocks with smooth surfaces and a particle size range of 1-9 microns; the particles of ZIF-8 are in regular polyhedral shapes and a particle size range of 220-280 nanometers; the number of faces of the regular polyhedron is not less than 6; both Zn-BTEC and ZIF-8 are formed by the coordination of organic ligands and metal ions; the organic ligands are selected from at least one of pyromellitic acid, N,N-dimethylformamide and 2-methylimidazole; the metal ions are from zinc oxide and / or zinc salt; the coupling agent used for coupling is selected from at least one of polyvinyl pyrrolidone and polyvinyl alcohol; the zinc salt is selected from at least one of zinc nitrate, zinc sulfate and zinc chloride. The hybrid nanocomposite material Zn‑BTEC@ZIF‑8 of the present invention is formed by coupling ZIF‑8 on the surface of Zn‑BTEC to form a stable structure with regular morphology. Compared with single Zn‑BTEC and ZIF‑8, it exhibits excellent selectivity and sensitivity in sensing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fluorescence detection, and in particular to a hybrid nanocomposite material Zn-BTEC@ZIF-8 and a preparation method thereof, and a fluorescence probe and a detection method thereof. Background Art

[0002] Histamine is a heterocyclic biogenic amine formed by the decarboxylation of the amino acid L-histidine. Foods with high protein content, especially some fish with green skin and red meat and their products, contain a large amount of histidine. If stored for a long time or improperly, they are very easy to spoil and produce histamine. Therefore, the histamine level is closely related to its freshness and can be used as an important indicator to evaluate the freshness of such foods. According to the World Health Organization, histamine is listed as an important cause in the evaluation of many food poisoning incidents. Many countries and organizations have stipulated the limit of His in fish and fish products. For example, China (GB 2733-2015) and Turkey both stipulate that the limit of histamine in fish should be less than 200 mg kg-1. Europe, Iran, Indonesia and Brazil require that the histamine content in fish should not exceed 100 mg kg-1. The US Food and Drug Administration (FDA) has set stricter limits on histamine in fish, stipulating that it should not exceed 50 mg kg-1.

[0003] Since excessive histamine levels in food do not affect the sensory properties of food, rapid quantitative detection of histamine in food is very necessary. The current standard detection methods for histamine mainly include capillary electrophoresis, gas chromatography, high performance liquid chromatography (HPLC) and enzyme-linked immunosorbent assay (ELISA). However, these methods generally have problems such as complex sample preparation, expensive instruments and long detection time.

[0004] Currently, optical biosensor platforms have attracted much attention. There are many types of optical biosensors based on absorbance, photoluminescence, surface enhanced Raman spectroscopy (SERS) and fluorescence. As one of the most popular strategies, fluorescent sensors can obtain selectivity through special reaction processes or functional groups, overcome the difficulties of complex detection environment, and many fluorescent probes have been used for rapid detection of histamine in food. For example, the rapid detection of histamine in fish based on the fluorescence activity of graphene phase carbon nitride (g-C3N4), and the use of carbon quantum dots (CQDs) and synthetic peptides, so that the fluorescence of carbon quantum dots is effectively quenched by peptides through electron transfer interactions. In the presence of histamine, the fluorescence will be restored due to the stronger interaction between peptides and targets.

[0005] The use of fluorescent nanomaterials can provide a better development environment for fluorescent sensors. However, these rapid detection methods require complex fluorescent probe compositions and preparation techniques. Therefore, it is expected to develop a simple, low-cost, and rapid method for detecting histamine in aquatic products. Metal-organic framework materials are a class of porous crystalline materials with broad application prospects. They can be prepared by combining different organic ligands with metal ions. Hybrid functionalized materials can make them show better stability, selectivity, and sensitivity in the detection of histamine. Some multi-emission metal-organic framework materials (MOFs) recognize amines through emission red shift, limit-induced enhancement, and energy transfer. In-depth research on multi-emission metal-organic framework materials (MOFs) has led to an emerging family of MOF-on-MOF hybrid materials, which are composed of two or more metal-organic framework materials (MOFs) units conjugated. Compared with a single metal-organic framework material (MOF), MOF-on-MOF shows excellent selectivity and sensitivity in sensing. In terms of histamine detection, the intelligent ratiometric fluorescence sensor F-10c⊂ZIF-8-on-In-dpda was further constructed by preparing a three-dimensional (3D) anionic fluorescent metal-organic framework (MOF) with controllable growth of ZIF-8 on the fluorescent core and synchronously encapsulating fluorescein to sense biogenic amines. However, after adding traditional organic dyes to inorganic materials, the luminescence of the hybrid material may be weakened or even quenched due to the polymerization quenching (ACQ) effect. Aggregation-induced emission is an effect that emits almost no light in dilute solution but shows strong fluorescence emission in the aggregated state. Due to the simple molecular structure, low background noise, high luminescence efficiency, good photostability and good biocompatibility of AIEgens, it has been applied in a series of electroluminescent devices, biological probes, chemical sensors and so on. However, there are no reports on luminescent sensors for the detection of biogenic amines based on hybrid metal-organic framework (MOF).

[0006] Therefore, a hybrid nanocomposite material and a fluorescence detection method for detecting the histamine content in fish are expected.

[0007] Based on this, the present invention synthesized a MOF-on-MOF nanomaterial Zn-BTEC@ZIF-8, and constructed a fluorescent probe Zn-BTEC@ZIF-8@Tet based on the strong fluorescence characteristics emitted by its aggregation-induced emission effect with tetracycline, and established a fluorescence method for detecting the histamine content in fish. The detection performance of the synthesized Zn-BTEC@ZIF-8@Tet heterostructure for histamine was studied through batch experiments and characterizations such as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), ultraviolet-visible-near infrared spectroscopy (UV-vis), and fluorescence (FL). A large number of test results show that Zn-BTEC@ZIF-8@Tet can quickly quantify the histamine level, providing ideas for simultaneous detection of integrated systems based on the design of multifunctional MOF-on-MOF heterostructures. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention provides a hybrid nanocomposite material Zn-BTEC@ZIF-8 and a preparation method thereof, a fluorescent probe and a detection method thereof. The hybrid nanocomposite material Zn-BTEC@ZIF-8 is a stable structure formed by coupling ZIF-8 on the surface of Zn-BTEC with a regular morphology. Compared with single Zn-BTEC and ZIF-8, the hybrid nanocomposite material Zn-BTEC@ZIF-8 exhibits excellent selectivity and sensitivity in sensing.

[0009] The first aspect of the present invention provides a hybrid nanocomposite material Zn-BTEC@ZIF-8, wherein the Zn-BTEC@ZIF-8 is formed by coupling ZIF-8 on the surface of Zn-BTEC;

[0010] The particles of Zn-BTEC are in the form of irregular blocks with smooth surfaces, and the particle size ranges from 1 to 9 microns, preferably from 3 to 7 microns;

[0011] The particles of ZIF-8 are regular polyhedrons with a particle size range of 220-280 nanometers, preferably 240-260 nanometers;

[0012] A regular polyhedron has at least 6 faces;

[0013] Both Zn-BTEC and ZIF-8 are formed by the coordination of organic ligands and metal ions;

[0014] The organic ligand is selected from at least one of pyromellitic acid, N,N-dimethylformamide and 2-methylimidazole;

[0015] The metal ions are derived from zinc oxides and / or zinc salts;

[0016] The coupling agent used for coupling is selected from at least one of polyvinyl pyrrolidone and polyvinyl alcohol;

[0017] The zinc salt is selected from at least one of zinc nitrate, zinc sulfate and zinc chloride.

[0018] The second aspect of the present invention provides a method for preparing the hybrid nanocomposite material Zn-BTEC@ZIF-8, comprising the following steps:

[0019] 1) Pyromellitic acid, zinc oxide, ultrapure water and N,N-dimethylformamide are mixed and ultrasonically treated, then transferred and sealed into a polytetrafluoroethylene autoclave for reaction. The reaction product is subjected to initial centrifugal separation, ultrasonic water washing, and centrifugal separation again to obtain a white solid. The white solid is washed with anhydrous ethanol and vacuum dried to obtain Zn-BTEC, which is then refrigerated and stored;

[0020] 2) dissolving Zn-BTEC in deionized water and ultrasonically treating the solution to obtain a uniform solution, adding polyvinyl pyrrolidone to the uniform solution and stirring to obtain a first mixture, dissolving zinc nitrate hexahydrate in water to obtain a second mixture, adding the second mixture to the first mixture and stirring to obtain a third mixture, dissolving 2-methylimidazole in water to obtain a fourth mixture, adding the fourth mixture to the third mixture, stirring, centrifuging, washing, and vacuum drying in sequence to obtain Zn-BTEC@ZIF-8, and / or,

[0021] The fourth mixture is added to the second mixture, and ZIF-8 is obtained after stirring, centrifugal separation, water washing and vacuum drying.

[0022] The third aspect of the present invention provides a fluorescent probe Zn-BTEC@ZIF-8@Tet for detecting histamine content in fish, wherein the Zn-BTEC@ZIF-8@Tet comprises:

[0023] 1) the above-mentioned Zn-BTEC@ZIF-8;

[0024] 2) Tetracycline hydrochloride;

[0025] 3) Tris-HCl buffer;

[0026] Based on the volume of Zn-BTEC@ZIF-8@Tet, the concentration of Zn-BTEC@ZIF-8 was 1.00-1.50 mg / L, and the concentration of tetracycline hydrochloride was 0.9-1.2 mM.

[0027] The fourth aspect of the present invention provides a fluorescence detection method for detecting the histamine content in fish, using the above-mentioned Zn-BTEC@ZIF-8@Tet to perform fluorescence detection on the histamine content in fish;

[0028] The linear range of fish histamine concentration detected by fluorescence was 2-1000 mg / L;

[0029] The detection limit of fluorescence detection is no more than 1.458 mg / L;

[0030] The excitation wavelength for fluorescence detection is 365-395 nm, preferably 380-390 nm.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention is a stable structure formed by coupling ZIF-8 on the surface of Zn-BTEC with a regular morphology. Compared with single Zn-BTEC and ZIF-8, it exhibits excellent selectivity and sensitivity in sensing.

[0033] 2. The preparation method of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention is simple, the cost of raw materials is low, and the prepared nanocomposite material Zn-BTEC@ZIF-8 has good consistency.

[0034] 3. The fluorescent probe Zn-BTEC@ZIF-8@Tet for detecting the histamine content in fish proposed in the present invention can quickly quantify the histamine level, the fluorescence intensity reaches stability within 20 minutes, the stable storage time exceeds 20 days, and it has strong selectivity and anti-interference ability.

[0035] 4. The fluorescent probe Zn-BTEC@ZIF-8@Tet for detecting the histamine content in fish proposed in the present invention competes with tetracycline hydrochloride in the aggregation-induced emission complex based on the unique interaction between histamine and Zn-BTEC@ZIF-8, resulting in quenching of fluorescence. Compared with existing methods, the sensor has a larger detection range and a lower detection limit. The detection limit of this method is 1.458 mg / L, which is better than many reported methods.

[0036] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.

[0038] Figure 1These are scanning electron microscope (SEM) images of Zn-BTEC, ZIF-8, and Zn-BTEC@ZIF-8 in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention (A, B, and C, respectively), a comparison chart of X-ray diffraction (XRD) spectra of Zn-BTEC, ZIF-8, and Zn-BTEC@ZIF-8 (D), a comparison chart of Fourier transform infrared spectroscopy (FTIR) (E), and a comparison chart of X-ray photoelectron spectroscopy (XPS) (F).

[0039] Figure 2 Schematic diagram of the preparation process of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention (A) and schematic diagram of the mechanism of the fluorescent probe Zn-BTEC@ZIF-8@Tet for histamine detection (B).

[0040] Figure 3 The X-ray photoelectron spectrum (XPS) diagram (A) of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention, the fluorescent probe Zn-BTEC@ZIF-8@Tet after the addition of histamine, the potential analysis diagram (B), the C1s orbital high-resolution X-ray photoelectron spectrum (XPS) diagram (C), the N 1s orbital high-resolution X-ray photoelectron spectrum (XPS) diagram (D), the O 1s orbital high-resolution X-ray photoelectron spectrum (XPS) diagram (E), and the Zn 2p orbital high-resolution X-ray photoelectron spectrum (XPS) diagram (F).

[0041] Figure 4 This is the aggregation-induced emission (AIE) effect mechanism diagram of the hybrid nanocomposite material Zn-BTEC@ZIF-8 combined with tetracycline hydrochloride (Tet) and Zn-BTEC@ZIF-8@Tet for histamine detection proposed in the present invention.

[0042] Figure 5 The fluorescent probe Zn-BTEC@ZIF-8@Tet of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention is a fluorescence spectrum of the probe in the presence of different concentrations of histamine (the curve from top to bottom represents an increase in the concentration of histamine), a relationship between the histamine concentration and the probe quenching efficiency at 525 nm (B), a specific analysis diagram of the fluorescence analysis (C), and a diagram of the change of the quenching efficiency of the fluorescence analysis over time (D).

[0043] Figure 6The figures are the C 1s orbital high-resolution X-ray photoelectron spectroscopy (XPS) graph (A), the N 1s orbital high-resolution X-ray photoelectron spectroscopy (XPS) graph (B), the O 1s orbital high-resolution X-ray photoelectron spectroscopy (XPS) graph (C), and the Zn 2p orbital high-resolution X-ray photoelectron spectroscopy (XPS) graph (D) of Zn-BTEC, ZIF-8 and Zn-BTEC@ZIF-8 in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention.

[0044] Figure 7 This is the nitrogen (N2) adsorption isotherm diagram of Zn-BTEC, ZIF-8 and Zn-BTEC@ZIF-8 in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention at 77 K.

[0045] Figure 8 It is a thermogravimetric analysis curve diagram of Zn-BTEC, ZIF-8 and Zn-BTEC@ZIF-8 in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention.

[0046] Fig. 9 The fluorescence spectra of Zn-BTEC in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention in the presence and absence of histamine (Zn-BTEC: 1 mg / mL; tetracycline hydrochloride (Tet) concentration: 1.5 mM; histamine concentration: 1000 mg / L; incubation time: 20 minutes) (A), the fluorescence spectra of ZIF-8 in the presence and absence of histamine (tetracycline hydrochloride (Tet) concentration: 1.5 mM; histamine concentration: 1000 mg / L; incubation time: 20 minutes) (B), the fluorescence spectra of Zn-BTEC@ZIF-8 in the presence and absence of histamine (tetracycline hydrochloride (Tet) concentration: 1.5 mM; histamine concentration: 1000 mg / L; incubation time: 20 minutes) (C), and the comparison of the quenching efficiency of Zn-BTEC, ZIF-8 and Zn-BTEC@ZIF-8 (D).

[0047] Fig.10 This is a transmission electron microscope (TEM) image of the fluorescent probe Zn-BTEC@ZIF-8@Tet in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention.

[0048] Fig.11These are the size distribution diagrams and comparison diagrams of Zn-BTEC, ZIF-8, Zn-BTEC@ZIF-8, fluorescent probe Zn-BTEC@ZIF-8@Tet, and fluorescent probe Zn-BTEC@ZIF-8@Tet with added histamine in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention (A, B, C, D, E, and F, respectively).

[0049] Fig.12 The fluorescence spectra of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention with and without the addition of histamine at a concentration of 1000 mg / L and a volume of 200 μL (A), the fluorescence spectra of tetracycline hydrochloride (Tet) with and without the concentration of 1000 mg / L and a volume of 200 μL histamine (B), and the fluorescence spectra of tetracycline hydrochloride (Tet) in the presence of different concentrations of histamine (C).

[0050] Fig.13 This is a color comparison chart of the fluorescent probe Zn-BTEC@ZIF-8@Tet (A) in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention, the fluorescent probe Zn-BTEC@ZIF-8@Tet after adding histamine (B), and the fluorescent probe Zn-BTEC@ZIF-8@Tet after adding histamine (C) when exposed to ultraviolet light for the same time.

[0051] Fig.14 This is a transmission electron microscope (TEM) image of the fluorescent probe Zn-BTEC@ZIF-8@Tet in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention being decomposed by histamine.

[0052] Fig.15 This is a graph showing the change in fluorescence intensity over time of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention after histamine is added.

[0053] Fig.16 This is a graph showing the change in fluorescence intensity over time of the fluorescent probe Zn-BTEC@ZIF-8@Tet in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention obtained by using fluorescence analysis method.

[0054] Fig.17 This is a graph showing the change in fluorescence intensity over time of the fluorescent probe Zn-BTEC@ZIF-8@Tet in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention after adding 500 mg / L histamine.

[0055] Fig.18This is the fluorescence spectrum of the fluorescent probe Zn-BTEC@ZIF-8@Tet in the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention at seven different excitation wavelengths (excitation wavelength: 365, 370, 375, 380, 385, 290, 395 nm, histamine concentration: 500 mg / L) after adding histamine (A) and the effect of different excitation wavelengths on the detection of histamine (B).

[0056] Fig.19 Figure 1 is the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention. The quenching efficiency of Zn-BTEC@ZIF-8 with different concentrations (1, 1.25, 1.5, 2, 2.5, 5, 10 mg / L) on histamine detection (histamine concentration: 1000 mg / L; incubation time: 0 min; incubation time: 40 min; tetracycline hydrochloride (Tet) concentration: 1.5 mM) in the presence (I) and absence (I0) of histamine (A). The quenching efficiency of tetracycline hydrochloride (Tet) with different concentrations (0.5, 1.0, 1.5, 2.0, 2.5, 3.0 mM) (histamine: 1000 mg / L; incubation time: 40 min; detection time: 40 min) in Zn-BTEC@ZIF-8 solutions with (I) and without (I0) histamine (B).

[0057] Fig. 20 This is a graph showing the influence of the concentration of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention on the quenching efficiency value of the fluorescent probe Zn-BTEC@ZIF-8@Tet (A), and a graph showing the influence of the concentration of tetracycline hydrochloride on the quenching efficiency value of the fluorescent probe Zn-BTEC@ZIF-8@Tet (B).

[0058] Fig.21 It is the Stern-Volmer plot of histamine detection of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention.

[0059] Fig. 22 This is a color comparison diagram of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention, the fluorescent probe Zn-BTEC@ZIF-8@Tet under ultraviolet irradiation (A), and the fluorescent probe Zn-BTEC@ZIF-8@Tet with histamine added under ultraviolet irradiation (B).

[0060] Fig.23 The hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention is used. After adding 500 mg / L histamine, the fluorescence intensity of the fluorescent probe Zn-BTEC@ZIF-8@Tet at 525 nm is repeatedly measured.

[0061] Fig.24This is a standard curve diagram of the hybrid nanocomposite material Zn-BTEC@ZIF-8 proposed in the present invention, which is used in a commercial ELISA detection kit for detecting histamine concentrations of 0.2 to 16 ng / mL. DETAILED DESCRIPTION

[0062] In order to make the present invention more easily understood, the present invention will be described in detail below in conjunction with the embodiments and the accompanying drawings. These embodiments are only for illustration and are not intended to limit the present invention.

[0063] According to a first aspect of the present invention, Figure 1 As shown in C, the present invention provides a hybrid nanocomposite material Zn-BTEC@ZIF-8, wherein the Zn-BTEC@ZIF-8 is formed by coupling ZIF-8 on the surface of Zn-BTEC;

[0064] The particles of Zn-BTEC are in the form of irregular blocks with smooth surfaces, and the particle size ranges from 1 to 9 microns, preferably from 3 to 7 microns;

[0065] The particles of ZIF-8 are regular polyhedrons with a particle size range of 220-280 nanometers, preferably 240-260 nanometers;

[0066] A regular polyhedron has at least 6 faces;

[0067] Both Zn-BTEC and ZIF-8 are formed by the coordination of organic ligands and metal ions;

[0068] The organic ligand is selected from at least one of pyromellitic acid, N,N-dimethylformamide and 2-methylimidazole;

[0069] The metal ions are derived from zinc oxides and / or zinc salts;

[0070] The coupling agent used for coupling is selected from at least one of polyvinyl pyrrolidone and polyvinyl alcohol;

[0071] The zinc salt is selected from at least one of zinc nitrate, zinc sulfate and zinc chloride.

[0072] In the present invention, the hybrid nanocomposite material Zn-BTEC@ZIF-8 is formed by coupling ZIF-8 on the surface of Zn-BTEC to form a stable structure with regular morphology. Compared with single Zn-BTEC and ZIF-8, it exhibits excellent selectivity and sensitivity in sensing.

[0073] According to a second aspect of the present invention, the present invention provides a method for preparing the above hybrid nanocomposite material Zn-BTEC@ZIF-8, comprising the following steps:

[0074] 1) Pyromellitic acid, zinc oxide, ultrapure water and N,N-dimethylformamide are mixed and ultrasonically treated, then transferred and sealed into a polytetrafluoroethylene autoclave for reaction. The reaction product is subjected to initial centrifugal separation, ultrasonic water washing, and centrifugal separation again to obtain a white solid. The white solid is washed with anhydrous ethanol and vacuum dried to obtain Zn-BTEC, which is then refrigerated and stored;

[0075] 2) dissolving Zn-BTEC in deionized water and ultrasonically treating the solution to obtain a uniform solution, adding polyvinyl pyrrolidone to the uniform solution and stirring to obtain a first mixture, dissolving zinc nitrate hexahydrate in water to obtain a second mixture, adding the second mixture to the first mixture and stirring to obtain a third mixture, dissolving 2-methylimidazole in water to obtain a fourth mixture, adding the fourth mixture to the third mixture, stirring, centrifuging, washing, and vacuum drying in sequence to obtain Zn-BTEC@ZIF-8, and / or,

[0076] The fourth mixture is added to the second mixture, and ZIF-8 is obtained after stirring, centrifugal separation, water washing and vacuum drying.

[0077] According to the present invention, in step 1), the molar numbers of pyromellitic acid and zinc oxide used are the same, both 1.3-3.5 mM;

[0078] The amount of ultrapure water used is 0.5-2 mL;

[0079] The amount of N,N-dimethylformamide used is 8-12 mL.

[0080] The duration of ultrasonic treatment was 5-20 min;

[0081] The reaction temperature is 160-200°C and the reaction time is 2.5-4.5 days.

[0082] Preferably, in step 1), ultrasonic washing is ultrasonic treatment after each washing, and the number of ultrasonic washing is not less than 3 times, and the time of each ultrasonic treatment is 5-15 minutes;

[0083] The speed of the initial centrifugation is 7000-9000 rpm and the time is 8-12 minutes;

[0084] The speed of the second centrifugation is 4000-6000 rpm, and the time is 2-8 minutes;

[0085] The number of washing with anhydrous ethanol shall not be less than 3 times;

[0086] The vacuum drying temperature is 40-60°C and the time is 12-24 hours;

[0087] The refrigerated storage temperature is 2-6℃.

[0088] According to the present invention, in step 2), the amount of Zn-BTEC used is 10-30 mg, and the amount of deionized water used is 8-12 mL;

[0089] The amount of zinc nitrate hexahydrate used is 0.3-0.7 g, and the amount of water used to dissolve zinc nitrate hexahydrate is 8-12 mL;

[0090] The amount of 2-methylimidazole used is 2.2-2.7 g, and the amount of water used to dissolve 2-methylimidazole is 8-12 mL.

[0091] Preferably, in step 2), the polyvinyl pyrrolidone is added to the uniform solution and stirred for 10-14 hours;

[0092] The second mixture is added to the first mixture and stirred for 2-6 hours;

[0093] The fourth mixture is added to the third mixture and stirred for 2-6 hours;

[0094] The speed of centrifugation is 7000-9000 rpm and the time is 8-12 minutes;

[0095] The number of water washes should be no less than 3 times, with a water consumption of 18-22 mL each time;

[0096] The vacuum drying temperature is 60-80°C and the time is 10-14 hours.

[0097] In the present invention, the preparation method of the hybrid nanocomposite material Zn-BTEC@ZIF-8 is simple, the cost of raw materials is low, and the prepared nanocomposite material Zn-BTEC@ZIF-8 has good consistency.

[0098] According to a third aspect of the present invention, the present invention provides a fluorescent probe Zn-BTEC@ZIF-8@Tet for detecting histamine content in fish, wherein the fluorescent probe Zn-BTEC@ZIF-8@Tet comprises:

[0099] 1) the above-mentioned Zn-BTEC@ZIF-8;

[0100] 2) Tetracycline hydrochloride;

[0101] 3) Tris-HCl buffer;

[0102] Based on the volume of Zn-BTEC@ZIF-8@Tet, the concentration of Zn-BTEC@ZIF-8 was 1.00-1.50 mg / L, and the concentration of tetracycline hydrochloride was 0.9-1.2 mM.

[0103] According to the present invention, the above-mentioned Zn-BTEC@ZIF-8@Tet is prepared by a method comprising the following steps:

[0104] 1) Add the aqueous solution of Zn-BTEC@ZIF-8 prepared by the above method into Tris-HCl buffer and mix well to obtain a buffer solution;

[0105] 2) Add tetracycline hydrochloride to the initial buffer solution and mix well to obtain Zn-BTEC@ZIF-8@Tet;

[0106] The pH of Tris-HCl buffer is 7-9;

[0107] Based on the volume of Zn-BTEC@ZIF-8@Tet, the concentration of Zn-BTEC@ZIF-8 was 1.00-1.50 mg / L, and the concentration of tetracycline hydrochloride was 0.9-1.2 mM.

[0108] In the present invention, the fluorescent probe Zn-BTEC@ZIF-8@Tet for detecting the histamine content in fish can quickly quantify the histamine level, the fluorescence intensity reaches stability within 20 minutes, the stable storage time exceeds 20 days, and it has strong selectivity and anti-interference ability.

[0109] According to a fourth aspect of the present invention, the present invention provides a fluorescence detection method for detecting the histamine content in fish, using the above-mentioned Zn-BTEC@ZIF-8@Tet to perform fluorescence detection on the histamine content in fish;

[0110] The linear range of fish histamine concentration detected by fluorescence was 2-1000 mg / L;

[0111] The detection limit of fluorescence detection is no more than 1.458 mg / L;

[0112] The excitation wavelength for fluorescence detection is 365-395 nm, preferably 380-390 nm.

[0113] In the present invention, the fluorescent probe Zn-BTEC@ZIF-8@Tet for detecting the histamine content in fish competes with tetracycline hydrochloride in the aggregation-induced emission complex based on the unique interaction between histamine and Zn-BTEC@ZIF-8, resulting in quenching of fluorescence. Compared with existing methods, the sensor has a larger detection range and a lower detection limit. The detection limit of this method is 1.458 mg / L, which is better than many reported methods.

[0114] The present invention will be described in detail below by way of examples.

[0115] Materials and reagents used in the examples of this application

[0116] All water used was ultrapure water (18 MΩ•cm); nano zinc oxide (purity 99.8%, 50±10 nm, Shanghai Aladdin Biochemical Reagent Co., Ltd.), pyromellitic acid (purity 98%, Shanghai Yien Chemical Technology Co., Ltd.), N,N-dimethylformamide (purity 99%, Shanghai Yien Chemical Technology Co., Ltd.), polytetrafluoroethylene reactor lining (25 mL), polyvinyl pyrrolidone (average molecular weight 58000, K29-32, Shanghai Aladdin Biochemical Reagent Co., Ltd.), zinc nitrate hexahydrate (purity 99%, Shanghai Hushi Laboratory Equipment Co., Ltd.), Tris-HCl buffer (1 mmol / L, pH 8.0) (Sigma-Aldrich, USA), 2-methylimidazole (purity 98%, Shanghai Yien Chemical Technology Co., Ltd.), tetracycline hydrochloride (Solarbio, purity 95%), and histamine (purity 98%, Shanghai Yuanye Biotechnology Co., Ltd.).

[0117] Instruments and equipment used in the examples of this application

[0118] F97pro fluorescence spectrophotometer (Shanghai Lingguang Technology Co., Ltd.); UH4150 UV-visible-near-infrared spectrophotometer (Hitachi, Japan); field emission scanning electron microscope (ZEISS Sigma 500); L-200 analytical balance (Mettler-Todori Instrument Co., Ltd., Switzerland); DH-101-0BY electric vacuum drying oven (Tianjin Zhonghuan Experimental Electric Furnace Co., Ltd.); SB25-12D ultrasonic cleaning machine (Ningbo Xinzhi Biotechnology Co., Ltd.). Example

[0119] MOF was synthesized by solvothermal method. Pyromellitic acid (2.5 mM, 0.6375 g), zinc oxide (2.5 mM, 0.2034 g), 1 mL ultrapure water and 10 mL N,N-dimethylformamide (DMF) were added to a beaker and ultrasonicated for 10 minutes. Then, they were transferred to a polytetrafluoroethylene container, which was then sealed in an autoclave and reacted at 180°C for 3.5 days. After the reaction was completed, the product was separated by centrifugation, washed with ultrapure water 3 times, ultrasonicated for 10 minutes each time, and centrifuged for 5 minutes (5000r / min). The obtained white solid product was then centrifuged, washed with anhydrous ethanol 3 times, and dried in a 50°C vacuum oven overnight to obtain Zn-BTEC. Finally, it was stored in a refrigerator at 4°C. Example

[0120] 0.5 g of zinc nitrate hexahydrate was dissolved in 10 mL of water and stirred continuously for 4 h. Then, 2.5 g of 2-methylimidazole was dissolved in 10 mL of water and quickly added to the above mixture. The mixture was stirred for 4 h, centrifuged for 10 min, washed 3 times with water (20 mL) and dried under vacuum at 70 °C to obtain ZIF-8. Example

[0121] 20 mg of Zn-BTEC synthesized in Example 1 was dissolved in 10 mL of deionized water and ultrasonically treated to form a uniform solution. Then, 20 mg of polyvinyl pyrrolidone was added and stirred for 12 hours. Then, 0.5 g of zinc nitrate hexahydrate was dissolved in 10 mL of water and added to the above mixture, and stirred continuously for 4 hours. Then, 2.5 g of 2-methylimidazole was dissolved in 10 mL of water and quickly added to the above mixture. The mixture was stirred for 4 hours, centrifuged for 10 minutes, washed 3 times with water (20 mL) and dried in vacuo at 70 ° C to obtain Zn-BTEC@ZIF. Example

[0122] The three MOFs synthesized in Examples 1-3 were dissolved in water to prepare a 1 mg / mL solution for later use. 300 μL of the three MOF solutions (1 mg / mL) were then added to 1.7 mL of Tris-HCl buffer (10 mM, pH = 8). Then, tetracycline hydrochloride (1.5 mM) was added to the above solution, and then 1 mg / mL of histamine solution was added to observe the fluorescence change value after addition. Three parallel controls were made for each test sample, and the fluorescence quenching efficiency was calculated by adding pure water as a control. Example

[0123] 200 μL of the fluorescent probe Zn-BTEC@ZIF-8@Tet configured in Example 4 was drawn into a centrifuge tube, and then 200 μL of histamine solution standard with different mass concentration gradients (2 mg / L, 20 mg / L, 50 mg / L, 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, 1000 mg / L) was added. After incubation at 25 °C for 20 min, the fluorescence was stabilized and then measured. Under 385 nm laser excitation, the fluorescence spectrum at 420-720 nm was collected by a fluorescence spectrophotometer, and the fluorescence intensity at 525 nm was recorded as I. Three groups of parallel controls were made for each test sample, and pure water was added as a control, which was recorded as I0 to calculate the fluorescence quenching efficiency. Three replicates were used for each experiment. The fluorescence quenching efficiency of (I0-I) / I0 was determined under the optimal conditions.

[0124] Test Example 1

[0125] In this test example, the particle size and morphology of the hybrid nanocomposite Zn-BTEC@ZIF-8 were characterized by scanning electron microscopy (SEM). Zn-BTEC has an irregular block structure with a size of about a few microns and a relatively smooth surface. Figure 1 As shown in A, this is consistent with the literature report. The ZIF-8 synthesized alone has a regular and uniform polyhedral shape with a uniform size distribution of about 250 nm, as shown in Figure 1 As shown in B. ZIF-8 was coupled to the Zn-BTEC surface by the MOF-on-MOF synthesis method to prepare Zn-BTEC@ZIF-8, as shown in Figure 1 C shows that the ZIF-8 particles are densely distributed on the nanoblocks. The ZIF-8 is small in size, which may be due to the Zn-BTEC nanoblocks reducing the surface energy and limiting the spatial growth of ZIF-8 during the synthesis process. The smaller ZIF-8 can enlarge the specific surface area and enhance the interaction sites with the target area. During this process, the size and morphology of Zn-BTEC did not change significantly.

[0126] In order to further confirm the formation of hybrid nanocomposite Zn-BTEC@ZIF-8, in situ X-ray diffraction (XRD) patterns (e.g. Figure 1 D) found that the main characteristic lattice planes of each MOF material appeared in the hybrid nanocomposite material Zn-BTEC@ZIF-8, which illustrates the crystal integrity and stability of Zn-BTEC@ZIF-8 during the interface coupling process. In addition, Figure 1Fourier transform infrared (FTIR) spectra were recorded at 4000-400 cm-1 by E. In Zn-BTEC, the broad peaks between 3000-3600 cm-1 belong to OH stretching, and the peaks around 1615 and 1400 cm-1 represent symmetric and asymmetric carboxylate stretching vibrations, indicating inconsistent coordination end-types of carboxylate groups. The difference between νas(COO) and νs(COO) of Zn-BTEC (215 cm-1) is smaller than that of Na4BTEC (95 cm-1), which is due to the fact that the carboxyl groups coordinated to Zn(II) atoms are monodentate and bidentate. Fourier transform infrared (FTIR) characterization of ZIF-8 showed characteristic peaks at 1307 cm-1, 1148 cm-1, and 994 cm-1 corresponding to the in-plane bending of the imidazole ring, and the characteristic peak at 423 cm-1 corresponding to the stretching of Zn-N. The stretching vibration of C=N was observed at 1572 cm-1, and the stretching vibrations of aromatic and aliphatic CH were also observed at 2932 cm-1 and 3129 cm-1. The Fourier transform infrared spectroscopy (FTIR) spectrum of Zn-BTEC@ZIF-8 also showed the presence of Zn-N bonds (424 cm-1), stretching vibrations of imidazole rings (1149 cm-1, 995 cm-1), stretching vibrations of C=N (1566 cm-1), and stretching vibrations of CH (2919 cm-1, 3172 cm-1). The broad peak at 3000-3600 cm-1 is from the stretching of OH, which is more diffuse and broader than that of ZIF-8. The stretching vibration of C=N is more significant at 1572 cm-1. The infrared characteristic peaks of both MOFs are covered in Zn-BTEC@ZIF-8.

[0127] The formation and chemical groups of the hybrid nanocomposite Zn-BTEC@ZIF-8 were further investigated using X-ray photoelectron spectroscopy (XPS). Figure 1 As shown in F, signals of C, N, O and Zn elements were detected in the measured spectra of these three MOFs. Since no other elements were added, the peak position of each element was fixed, but the content of each element changed. X-ray photoelectron spectroscopy (XPS) relative content analysis showed that the C and N contents of the hybrid nanocomposite Zn-BTEC@ZIF-8 were lower than those of the individual MOFs, while the O content was higher than that of the individual MOFs, as shown in Table 1. The high-resolution X-ray photoelectron spectroscopy (XPS) spectra of C1s, O 1s, N 1s and Zn 2p of Zn-BTEC, ZIF-8 and Zn-BTEC@ZIF-8 were compared to analyze their chemical states and surface bonding information, such as Figure 3CF is shown in Figure 3. The C 1s XPS spectrum of Zn-BTEC@ZIF-8 is divided into three peaks at 284.7 eV, 285.9 eV and 288.6 eV, corresponding to CC, CO / CN and OCO, respectively. The O 1s XPS spectrum is fitted into two peaks at 531.8 and 532.4 eV, corresponding to CO and C=O of Zn-BTEC and ZIF-8, respectively. All changes in the binding energy of electrons C1s and O1s in the complex spectrum are evidence of the redistribution of electron density in the OCO segment caused by the complexation of metal ions by ligand oxygen atoms. By comparing with the bond energy of CN and C=N in ZIF-8, the bond energy of Zn-BTEC@ZIF-8 shifts to a higher binding energy. The N1 s XPS spectrum in Zn-BTEC@ZIF-8 is fitted into two peaks at 399 and 400.6 eV, corresponding to CN and C=N of the imidazole ring in ZIF-8. Compared with ZIF-8, its bond energy also changes to a higher binding energy. Combining the changes in the binding energy in Zn-BTEC@ZIF-8 with the binding energy of Zn-BTEC and ZIF-8 alone, it can be found that in the formed Zn-BTEC@ZIF-8, due to the electronic properties of the interface between Zn-BTEC and ZIF-8, there is a certain interaction between Zn-BTEC and ZIF-8. In addition, the X-ray photoelectron spectra (XPS) of Zn 2p3 / 2 and Zn 2p1 / 2 are given, with two peaks respectively. The Zn-BTEC@ZIF-8 nanocomposite material shows obvious coexistence of N 1s and O1s signals, in which the O element of Zn-BTEC@ZIF-8 mainly comes from OCO in Zn-BTEC, and the N element mainly comes from CN and C=N in 2-methylimidazole.

[0128]

[0129] Test Example 2

[0130] This test case tests the formation mechanism of Zn-BTEC@ZIF-8. The N2 adsorption-desorption isotherms of Zn-BTEC, ZIF-8 and Zn-BTEC@ZIF-8 are shown in Figure 2. Figure 7 The BET specific surface areas of the three MOFs are 36.92 m2 / g, 967.9695 m2 / g, and 409.6026 m2 / g, respectively. The specific surface area of ​​Zn-BTEC@ZIF-8 is lower than that of ZIF-8, which may be due to the partial embedding of Zn-BTEC in ZIF-8. The loading of ZIF-8 can increase the adsorption specific surface area of ​​the target to be tested, as shown in Table 2. Figure 8Thermogravimetric analysis (TGA) curves of Zn-BTEC, ZIF-8 and Zn-BTEC@ZIF-8. It can be clearly seen that the mass loss of synthesized Zn-BTEC@ZIF-8 can be divided into three main stages. The first stage is the evaporation of water molecules and the degradation of Zn-BTEC (<250℃). The second phase temperature is between 250~550℃, with a small mass loss (about 10%). Comparing the TGA curves of Zn-BTEC and ZIF-8, the main reason is the slow decomposition of ZIF-8. Then the third stage is from 550℃ to 800℃. It is attributed to the decomposition of ZIF-8. However, the trend of the graph of Zn-BTEC@ZIF-8 is milder than that of Zn-BTEC, which further confirms that the mass loss of Zn-BTEC is reduced when ZIF-8 is covered on the surface of Zn-BTEC, indicating that ZIF-8 is successfully attached to Zn-BTEC.

[0131]

[0132] Test Example 3

[0133] This test case uses fluorescence spectroscopy to study the optical properties of Zn-BTEC, ZIF-8, and Zn-BTEC@ZIF-8 hybrid nanocomposites and the performance of the constructed fluorescent probe. It is worth noting that the three MOF materials themselves do not have fluorescence, but after adding tetracycline hydrochloride (Tet), strong fluorescence emission occurs, such as Fig. 9 As shown (where Fig. 9 The three curves A, B, and C in the figure represent the fluorescence spectra of the probe of the MOF material, the probe of the MOF material with histamine added, and the MOF material itself from top to bottom). When tetracycline hydrochloride (Tet) is added, the full spectrum of the X-ray photoelectron spectroscopy (XPS) does not change significantly, such as Figure 3 As shown in A, it shows that there is no chemical reaction between Zn-BTEC@ZIF-8 and tetracycline hydrochloride (Tet). Fig.10 It can be seen that after the introduction of tetracycline hydrochloride (Tet), the morphology of Zn-BTEC@ZIF-8 was well maintained and the skeleton structure did not deform. Fig.11 Dynamic light scattering analysis showed that the particle size of Zn-BTEC@ZIF-8 increased after the addition of tetracycline hydrochloride (Tet). The results of zeta potential showed that the absolute value of the zeta potential of Zn-BTEC@ZIF-8@Tet (-7.5371 mV) was reduced by nearly half compared with the absolute value of Zn-BTEC@ZIF-8 (-14.1 mV) after the addition of tetracycline hydrochloride (Tet). Figure 3As shown in B. Through electrostatic interaction, the added tetracycline hydrochloride (Tet) can interact with Zn-BTEC@ZIF-8 to form aggregates. In addition, X-ray photoelectron spectroscopy (XPS) further confirmed the formation of aggregates. The increase in the carbon and oxygen content in Zn-BTEC@ZIF-8@Tet confirms that tetracycline hydrochloride (Tet) is adsorbed on the surface of Zn-BTEC@ZIF-8, or that tetracycline hydrochloride (Tet) enters the skeleton of Zn-BTEC@ZIF-8. After the addition of tetracycline hydrochloride (Tet), the relative content of CC in the C 1s XPS spectrum ( Figure 3 The relative content of C in the N 1s XPS spectrum decreased from 62.73% to 28.74%, the relative content of CO / CN increased from 23.30% to 45.69%, and the relative content of C=O increased from 13.96% to 25.57% (Table 3). This reveals that during the formation of the fluorescent probe, electrons were redistributed due to the presence of π-π interactions. In addition, the relative content of CN in the N 1s XPS spectrum decreased from 70.33% to 59.08% ( Figure 3 D). It is speculated that this phenomenon is caused by the complexation of Zn nodes with N in Zn-BTEC@ZIF-8. The high-resolution XPS spectrum of O 1s is mainly composed of two peaks, corresponding to CO and C=O bands. After adding tetracycline, the relative content of CO decreased from 62.01% to 43.59%, and the relative content of C=O decreased from 37.99% to 32.39%, and was converted into OH. This is due to the hydrogen bond interaction between -COOH / -OH of tetracycline hydrochloride and -NH2 / -COOH in Zn-BTEC@ZIF-8 during the formation of the probe. XPS spectrum of O 1s ( Figure 3 The decrease in the relative content of CO and C=O converted to OH by E) is due to the hydrogen bond interaction between -NH2 / -OH and -NH2 / -COOH of Tet in Zn-BTEC@ZIF-8 during the probe composition process. From the above discussion, it can be seen that Zn-BTEC@ZIF-8 interacts with tetracycline hydrochloride (Tet) through hydrogen bonds, π-π interactions, and the coordination of Zn atoms and N in tetracycline hydrochloride (Tet), and the excellent void structure of Zn-BTEC@ZIF-8 provides adsorption sites for tetracycline hydrochloride (Tet) to aggregate in the pores of MOF. During the polymerization process, intramolecular rotation is restricted or the intramolecular rotation restriction process is activated, thereby turning on the fluorescence emission of the luminogen, which is why it can be used as a fluorescent probe.

[0134]

[0135] During the synthesis process, Zn-BTEC was used as the host of MOF-on-MOF, and ZIF-8 was used as an ideal guest to prepare various nanomaterials. Both Zn-BTEC and ZIF-8 could induce luminescence by polymerization with tetracycline hydrochloride (Tet) alone, and the larger particles of Zn-BTEC could provide more loading sites for ZIF-8. ZIF-8 has abundant micro-mesopores and a large specific surface area, which can provide more space for tetracycline hydrochloride (Tet) and produce an aggregation-induced luminescence effect with tetracycline hydrochloride (Tet). After histamine was attached, the fluorescence intensity of the three MOFs decreased. Fig. 9 As shown. For the detection of histamine, the quenching efficiency (QE) of Zn-BTEC is (45.2388±0.7727)%, that of ZIF-8 is (52.1830±1.8860)%, and that of Zn-BTEC@ZIF-8 is (62.8548±1.7765)%. The QE differences among the three MOFs are statistically significant (p<0.001). The QE of Zn-BTEC@ZIF-8 is higher than that of Zn-BTEC and ZIF-8 (p<0.001).

[0136] Fluorescence determination of histamine using Zn-BTEC@ZIF-8 and tetracycline hydrochloride (Tet) respectively. Fig.12 As shown (where Fig.12 The curves in C represent the fluorescence spectra of histamine concentrations from high to low from top to bottom). MOF and histamine have no fluorescence emission, while the mixture of tetracycline hydrochloride (Tet) and histamine has an obvious fluorescence signal. At the same time, it can be found that the color deepens immediately, which shows that tetracycline hydrochloride (Tet) plays an important role in the construction of polymerization-induced emission probes. The special structure of tetracycline hydrochloride (Tet) contains a large number of Lewis acid-base sites, which can provide a large number of proton donor-acceptor pairs and easily form hydrogen bonds. Histamine is positively charged when dissolved in water, and the aqueous solution is the basis for the protonation of aliphatic amino groups (pKa = 9.8). The π-π interaction between the benzene ring of the tetracycline hydrochloride (Tet) molecule and the imidazole ring of histamine brings them closer, effectively restricting the rotation of the aromatic ring in tetracycline hydrochloride (Tet), further increasing the green fluorescence, accompanied by a color change visible to the naked eye, and even undergoing a browning reaction under ultraviolet light, such as Fig.13 As shown in Figure 1, a series of concentration gradient histamine solutions reacted with tetracycline hydrochloride (Tet), but no obvious fluorescence signal could be obtained when low concentration histamine reacted only with tetracycline hydrochloride (Tet).

[0137] It is worth noting that the zeta potential test of Zn-BTEC@ZIF-8 showed that it was negatively charged, and the same was true for the synthesized Zn-BTEC@ZIF-8@Tet. There was a strong π-π interaction between the benzene ring of the host MOF Zn-BTEC and the imidazole ring of histamine, as well as hydrogen bonding between the guest ZIF-8 and histamine. XPS results showed that after the addition of histamine, the OCO (C 1s) area of ​​Zn-BTEC decreased from 25.57% to 4.27% (e.g. Figure 1 C), C=O (O 1s) also completely disappears ( Figure 3 E), indicating that its carboxyl group may be destroyed. It is speculated that hydrogen bonding interactions are formed between the H on the histamine amino group in MOF and the O on the carboxyl group. At the same time, the H of the amino group also forms hydrogen bonds with the N of the pyridine ring of ZIF-8. Therefore, these interactions may have caused some bonds in the Zn-BTEC@ZIF-8@Tet structure to change. This speculation is supported by the transmission electron microscopy (TEM) results after the reaction ( Fig.14 ) support, after the addition of histamine, only dispersed fragments were observed in the TEM image, and the MOF structure was destroyed. The zeta potential results also showed that the zeta potential after the addition of histamine (-9.193 mV) was slightly increased compared with Zn-BTEC@ZIF-8@Tet (-7.5371 mV) ( Figure 3 B), confirming that the condensed Zn-BTEC@ZIF-8@Tet becomes dispersed. The area of ​​the main peak in the Zn 2p XPS spectrum decreases, while the proportion of the satellite peaks increases ( Figure 3 F), indicating that the binding energy of 1023.13 eV at this site may be caused by Zn-N coordination. The synthesized Zn-BTEC@ZIF-8 is like a container, which can attract tetracycline hydrochloride (Tet) into the container through hydrogen bonds, π-π interactions and coordination. At this time, the aggregation-induced emission luminescence effect will occur, and the addition of histamine will destroy the container of Zn-BTEC@ZIF-8, and the loaded tetracycline hydrochloride (Tet) cannot aggregate, so the fluorescence intensity decreases, such as Figure 4 shown.

[0138] Test Example 4

[0139] This test case optimizes the effects of reaction time, excitation wavelength, and the concentrations of Zn-BTEC@ZIF-8 and tetracycline hydrochloride on fluorescence values. Using orthogonal experimental design (L20 matrix), four variables, MOF concentration (factor A) and tetracycline hydrochloride concentration (factor B), were analyzed, and it was found that these two variables had a significant effect on the quenching efficiency value of the fluorescent probe parameters. The matrix consists of two factors, with four and five levels respectively. The selected MOF was configured with different concentrations (5.0 mg / mL, 2.5 mg / mL, 1.25 mg / mL, 1 mg / mL) and tetracycline hydrochloride concentrations (1.0 mM, 1.5 mM, 2.0 mM, 2.5 mM, 3.0 mM) to prepare fluorescent probes, and the quenching efficiency of probe combinations with different concentrations was compared to obtain the optimal probe concentration. According to the principle of orthogonality, the design The matrix was tested to investigate its effect on the quenching efficiency value of the fluorescent probe.

[0140] Calculation of fluorescence quenching efficiency:

[0141] Calculation of collection probe fluorescence quenching efficiency:

[0142] The fluorescence spectra of the probe before and after the addition of histamine solution (excitation wavelength is 385 nm) were collected, and the quenching efficiency (%) was calculated as follows:

[0143] I 0 refers to the original fluorescence intensity without the sample to be tested, and I refers to the fluorescence intensity after exposure to the sample.

[0144] Before using the probe for detection, first optimize the probe's stability time and incubation time. Fig.15 It can be seen that the Zn-BTEC@ZIF-8@Tet fluorescent probe reaches stability in 20 min, and the fluorescence stability of the probe is measured, and it is found that its fluorescence can remain stable for 20 days under light-proof conditions, such as Fig.16 After adding histamine to the prepared probe sheet, the fluorescence can be turned off immediately, slightly decreased with the incubation time, and stabilized at 20 min, as shown in Fig.17 As shown. In addition, the fluorescence behavior of Zn-BTEC@ZIF-8@Tet as a fluorescent probe for the detection of histamine was studied by recording the fluorescence emission spectra at different excitation wavelengths of 365-395 nm. The fluorescence intensity gradually increased and reached a maximum at 385 nm, while the emission peak at 525 nm remained unchanged, as shown Fig.18 shown.

[0145] like Fig. 20As shown in Table 4-5, the quenching efficiency values ​​of fluorescent probes at different concentrations are significantly different. When the MOF concentration is 1.25 mg / L and the tetracycline hydrochloride (Tet) concentration is 1.0 mM, the quenching efficiency is the highest (A2B1), as shown in Table 4-5. By comparing the mean square values ​​corresponding to different factors, it is found that the MOF concentration (MS = 535.585) is greater than the tetracycline hydrochloride (Tet) concentration (MS = 98.214). The concentration change of MOF with a larger MS value will significantly affect the quenching efficiency of the fluorescent probe, while the concentration of tetracycline hydrochloride (Tet) with a smaller MS value has little effect on the quenching efficiency of the fluorescent probe.

[0146]

[0147]

[0148]

[0149] Test Example 5

[0150] This test example tests the effect of the probe Zn-BTEC@ZIF-8@Tet in quantitatively detecting histamine. Figure 5A shows the spectral response of the probe Zn-BTEC@ZIF-8@Tet to different concentrations of histamine, showing a characteristic emission band at 525 nm. As the histamine concentration increases, the fluorescence intensity of Zn-BTEC@ZIF-8@Tet decreases significantly. The emission intensity is logistically correlated with the histamine concentration in the range of 2-1000 mg / L. The difference in fluorescence intensity between the fluorescence value and the control fluorescence value is 0.9978, and in the range of 2-400 mg / L, (I 0 -I) / I*100 has a good linear correlation with histamine concentration (R2 = 0.9978) (Figure 5B). The obtained equation is (I 0 -I) / I *100=4.899+0.1279C, where I0 and I are the fluorescence intensities of Zn-BTEC@ZIF-8@Tet in the absence and presence of histamine, respectively. According to the calibration equation, histamine can be quantitatively detected. According to the definition of 3 times the blank signal deviation (3σ), the estimated detection limit (LOD) is 1.458 mg / L. Compared with traditional quenched fluorescent probes, it has higher sensitivity and wider linear range for detecting histamine. Compared with most reported histamine sensors, it has lower detection limit and wider detection range, and can be applied to the detection of fish with high histamine.

[0151] In the present invention, the Stern-Volmer (SV) equation is used , quantitatively study the quenching efficiency, where Ksv is the quenching constant (M −1). It can be observed in Figure 21 that it shows a good linear correlation, with a correlation coefficient (R2) of 0.9904, and the Ksv value of Zn-BTEC@ZIF-8@Tet is calculated to be 2.380×103 M -1 At the same time, the yellow-green fluorescence of the solution under ultraviolet light gradually fades and is visible to the naked eye ( Fig. 22 ).

[0152] In this test case, putrescine, cadaverine, β-phenylethylamine, histidine, MgCl, KCl, glucose and other substances were selected as interfering agents to investigate the selectivity and anti-interference ability of this method. The data were analyzed using SPSS software. Figure 5C shows that all interferons are significantly different from histamine (p<0.05). Due to the presence of imidazole rings in the structure of histamine, it contains primary amines, secondary amines, and tertiary amines. In aqueous solution, secondary amines have the highest alkalinity, and the dissociation constant of histamine (pKa=9.8) is higher than that of its main analogs, such as cadaverine (pKa=9.13), putrescine (pKa=9.35), and β-phenylethylamine (pKa=9.33). They are all primary amines, and there is an electron-withdrawing effect of the aromatic ring in β-phenylethylamine, which has weaker alkalinity and weaker attraction with the fluorescent probe.

[0153] This test case studies the signal reproducibility of the Zn-BTEC@ZIF-8@Tet fluorescent probe and its parallel response to multiple histamine samples of the same concentration. Fig.23 As shown in Figure 5, the fluorescence intensity after quenching remained basically unchanged in 8 repeated measurements, indicating that the developed Zn-BTEC@ZIF-8@Tet fluorescent probe has good signal reproducibility and can ensure the accurate detection of histamine. Figure 5D shows that the fluorescent probe can have an obvious stabilization effect within 20 days. The CV range of the daytime fluorescence response signal is 0.5874% ~ 4.887%, and the average CV is 2.455%. These results show that the Zn-BTEC@ZIF-8@Tet fluorescent probe has good long-term stability and high repeatability in the quantitative detection of histamine.

[0154] In this test case, the Zn-BTEC@ZIF-8@Tet nanoprobe was used to detect histamine in different fish samples to evaluate its reliability. The tuna samples in this test case were purchased from a local supermarket in Tianjin, China. The sample processing method is as follows: Use a meat grinder to mince the sample into a homogenate, mix 10 g of the homogenate sample with 20 mL of ultrapure water, and shake for 5 minutes. After centrifugation (10000 rpm, 10 minutes), filter and store the supernatant at 4°C for subsequent use. Subsequently, a certain concentration of histamine solution was added to the above sample, and the prepared Zn-BTEC@ZIF-8@Tet nanoprobe was used to quantify the histamine solution, and the detection results were compared using ELISA.

[0155] In order to verify the possibility of the method of the present invention to detect histamine in actual samples, the fluorescent probe was used to quantitatively detect histamine in fish. The concentration of histamine was determined by calculating the initial fluorescence and the fluorescence intensity after detection, and then using the linear calibration graph to interpolate the measured fluorescence intensity, and the results shown in Table 7 are expressed. The results obtained by this method were not statistically different from those obtained by the enzyme-linked immunosorbent assay (Figure 24), indicating that the sensing application of this method in complex actual samples is accurate and feasible. For comparison, other methods for detecting histamine using MOF are summarized in Table 8. It can be seen from the results that the LOD obtained by the method of the present invention is lower, and the detection time is shorter and more convenient.

[0156]

[0157] Analysis of sample detection differences: The histamine content in the samples was determined by Zn-BTEC@ZIF-8@Tet fluorescent probe and ELISA method. IBM SPSS Statistics 27 was used to perform a paired t-test to distinguish the data differences between the two methods. The results in Table S7 showed that there was no difference between the two methods (t =1.626, p>0.05).

[0158]

[0159] It can be seen from Test Examples 1-8 that the Zn-BTEC@ZIF-8@Tet fluorescent probe established in the embodiment is suitable for sensitive detection of histamine in seafood. The responsiveness of the formed MOF-on-MOF hybrid material is better than that of a single MOF material. The mechanism is based on the unique interaction between histamine and Zn-BTEC@ZIF-8, which competes with tetracycline hydrochloride in the aggregation-induced emission complex, resulting in quenching of fluorescence. Compared with existing methods, the sensor has a larger detection range and a lower detection limit. The detection limit of this method is 1.458 mg / L, which is better than many reported methods. This method has been applied to the determination of histamine in fish samples. By combining the special and excellent properties of MOF, further progress in the fields of analysis and materials research has been promoted.

[0160] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A hybrid nanocomposite material Zn-BTEC@ZIF-8, characterized in that: The Zn-BTEC@ZIF-8 is formed by coupling ZIF-8 on the surface of Zn-BTEC; The particles of Zn-BTEC are irregular blocks with smooth surfaces, and their particle sizes range from 1 to 9 microns; The particles of ZIF-8 are regular polyhedrons, and their particle size ranges from 220 to 280 nanometers; A regular polyhedron has at least 6 faces; Both Zn-BTEC and ZIF-8 are formed by the coordination of organic ligands and metal ions; The organic ligand is selected from at least one of pyromellitic acid, N,N-dimethylformamide and 2-methylimidazole; The metal ions are derived from zinc oxides and / or zinc salts; The coupling agent used for coupling is selected from at least one of polyvinyl pyrrolidone and polyvinyl alcohol; The zinc salt is selected from at least one of zinc nitrate, zinc sulfate and zinc chloride.

2. The hybrid nanocomposite material Zn-BTEC@ZIF-8 according to claim 1, characterized in that The particle size of the Zn-BTEC is in the range of 3-7 microns; The particle size of the ZIF-8 is in the range of 240-260 nanometers.

3. The method for preparing the hybrid nanocomposite material Zn-BTEC@ZIF-8 according to claim 1 or 2, characterized in that: The following steps are involved: 1) Pyromellitic acid, zinc oxide, ultrapure water and N,N-dimethylformamide are mixed and ultrasonically treated, then transferred and sealed into a polytetrafluoroethylene autoclave for reaction. The reaction product is subjected to initial centrifugal separation, ultrasonic water washing, and centrifugal separation again to obtain a white solid. The white solid is washed with anhydrous ethanol and vacuum dried to obtain Zn-BTEC, which is then refrigerated and stored; 2) dissolving Zn-BTEC in deionized water and ultrasonically treating the solution to obtain a uniform solution, adding polyvinyl pyrrolidone to the uniform solution and stirring to obtain a first mixture, dissolving zinc nitrate hexahydrate in water to obtain a second mixture, adding the second mixture to the first mixture and stirring to obtain a third mixture, dissolving 2-methylimidazole in water to obtain a fourth mixture, adding the fourth mixture to the third mixture, stirring, centrifuging, washing, and vacuum drying in sequence to obtain Zn-BTEC@ZIF-8, and / or, The fourth mixture is added to the second mixture, and ZIF-8 is obtained after stirring, centrifugal separation, water washing and vacuum drying.

4. The method for preparing the hybrid nanocomposite material Zn-BTEC@ZIF-8 according to claim 3, characterized in that: In step 1), the molar concentrations of pyromellitic acid and zinc oxide are the same, both 1.3-3.5 mM; The amount of ultrapure water used is 0.5-2 mL; The amount of N,N-dimethylformamide used is 8-12 mL.

5. The method for preparing the hybrid nanocomposite material Zn-BTEC@ZIF-8 according to claim 3, characterized in that: In step 1), the ultrasonic treatment time is 5-20 minutes; The reaction temperature is 160-200°C and the reaction time is 2.5-4.5 days.

6. The method for preparing the hybrid nanocomposite material Zn-BTEC@ZIF-8 according to claim 3, characterized in that: In step 1), ultrasonic washing is performed after each washing, and the number of ultrasonic washings is not less than 3 times, and the time of each ultrasonic treatment is 5-15 minutes; The speed of the initial centrifugation is 7000-9000 rpm and the time is 8-12 minutes; The speed of the second centrifugation is 4000-6000 rpm, and the time is 2-8 minutes; The number of washing with anhydrous ethanol shall not be less than 3 times; The vacuum drying temperature is 40-60°C and the time is 12-24 hours; The refrigerated storage temperature is 2-6℃.

7. The method for preparing the hybrid nanocomposite material Zn-BTEC@ZIF-8 according to claim 3, characterized in that: In step 2), the amount of Zn-BTEC is 10-30 mg, and the amount of deionized water is 8-12 mL; The amount of zinc nitrate hexahydrate used is 0.3-0.7 g, and the amount of water used to dissolve zinc nitrate hexahydrate is 8-12 mL; The amount of 2-methylimidazole used is 2.2-2.7 g, and the amount of water used to dissolve 2-methylimidazole is 8-12 mL.

8. The method for preparing the hybrid nanocomposite material Zn-BTEC@ZIF-8 according to claim 3, characterized in that: In step 2), polyvinyl pyrrolidone is added to the homogeneous solution and stirred for 10-14 hours; The second mixture is added to the first mixture and stirred for 2-6 hours; The fourth mixture is added to the third mixture and stirred for 2-6 hours; The speed of centrifugation is 7000-9000 rpm and the time is 8-12 minutes; The number of water washes should be no less than 3 times, with a water consumption of 18-22 mL each time; The vacuum drying temperature is 60-80°C and the time is 10-14 hours.

9. A fluorescent probe Zn-BTEC@ZIF-8@Tet for detecting histamine content in fish, characterized in that: The Zn-BTEC@ZIF-8@Tet comprises: 1) Zn-BTEC@ZIF-8 as described in any one of claims 1-2; 2) Tetracycline hydrochloride; 3) Tris-HCl buffer; The fluorescent probe Zn-BTEC@ZIF-8@Tet is prepared by a method comprising the following steps: 1) adding the aqueous solution of Zn-BTEC@ZIF-8 described in any one of claims 1 to 2 into Tris-HCl buffer and mixing to obtain a buffer initial solution; 2) Add tetracycline hydrochloride to the initial buffer solution and mix well to obtain Zn-BTEC@ZIF-8@Tet; The pH of Tris-HCl buffer is 7-9; Based on the volume of Zn-BTEC@ZIF-8@Tet, the concentration of Zn-BTEC@ZIF-8 was 1.00-1.50 mg / L, and the concentration of tetracycline hydrochloride was 0.9-1.2 mM.

10. A fluorescence detection method for detecting the histamine content in fish, characterized in that: Using the Zn-BTEC@ZIF-8@Tet described in claim 9 to perform fluorescence detection on the histamine content of fish; The linear range of fish histamine concentration detected by fluorescence was 2-1000 mg / L; The detection limit of fluorescence detection is no more than 1.458 mg / L; The excitation wavelength for fluorescence detection was 365-395 nm.

11. The fluorescence detection method for detecting the histamine content in fish according to claim 10, characterized in that: The excitation wavelength for fluorescence detection was 380-390 nm.